The Market Price of Risk - Schilbred, Cornelius M. (Review of Economic Studies, 1973)
Journal Article The Market Price of Risk Get access Cornelius M. Schilbred Cornelius M. Schilbred The Norwegian School of Economics and Business Administration Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 2, April 1973, Pages 283–292, https://doi.org/10.2307/2296654 Published: 01 April 1973